2010
DOI: 10.1007/978-3-642-14061-7_7
|View full text |Cite
|
Sign up to set email alerts
|

Estimating 3D Pose via Stochastic Search and Expectation Maximization

Abstract: Abstract. In this paper an approach is described to estimate 3D pose using a part based stochastic method. A proposed representation of the human body is explored defined over joints that employs full conditional models learnt between connected joints. This representation is compared against a popular alternative defined over parts using approximated limb conditionals. It is shown that using full limb conditionals results in a model that is far more representative of the original training data. Furthermore, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…A limitation with these approaches is that they are iterative and need convergence for a solution to be found. As noted in [30,31], this convergence happens in a particular order for objects modeled as a kinematic chain. Typically, those parts nearer a fixed node must converge before parts further down the model can do so.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…A limitation with these approaches is that they are iterative and need convergence for a solution to be found. As noted in [30,31], this convergence happens in a particular order for objects modeled as a kinematic chain. Typically, those parts nearer a fixed node must converge before parts further down the model can do so.…”
Section: Introductionmentioning
confidence: 93%
“…However, as the connection between parts is soft, the model is less constrained and slippage can occur, where two limbs can be joined at a very unlikely location or may not even be physically joined. It has been shown that given a known root location, models that have fixed joint positions outperform loose-limbed models at estimating 3D pose [31].…”
Section: Introductionmentioning
confidence: 99%
“…Human motion capture and activity recognition have proved viable in, for example, computer graphics, media production, robotics, and video surveillance applications throughout the years [25,20,1,27,5,26,18,7,8], though it still remains an open and challenging problem. There is however already a body of work interested in the detection and recognition of social interaction between multiple people [11,14], which is particularly difficult since the actions of multiple subjects must be inferred and understood.…”
Section: Introductionmentioning
confidence: 99%
“…According to [17], the main strategies for model-based poseestimation usually are global optimization such as interactive simulated annealing [18], filtering/smoothing/prediction such as Kalman filtering or particle filtering, local optimization such as iterative closest point (ICP) or a combination of these strategies such as in Juergen et al [17]. In [19], they represented the human body as a probability graphical model just as the one in [4,5,6,7,8] but adding some constraints between connected parts and called it Fixed Joint Model (FJM). This new representation helps the convergence of the global sampling process to go faster.…”
Section: Introductionmentioning
confidence: 99%